DESIGN, IMPLEMENTATION AND VERIFICATION OF SOFTWARE CODE FOR RADIATION DOSE ASSESSMENT BASED ON SIMPLE GENERIC ENVIRONMENTAL MODEL - Susila, I Putu; Yuniarto, Arif (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2017)
Radiation dose assessment to determine the potential of radiological impacts of various installations within nuclear facility complex is necessary to ensure evironmental and public safety. A simple generic model-based method for calculating radiation doses caused by the release of radioactive substances into the environment has been published by the International Atomic Energy Agency (IAEA) as the Safety Report Series No. 19 (SRS-19). In order to assist the application of the assessment method and a basis for the development of more complex assessment methods, an open-source based software code has been designed and implemented. The software comes with maps and is very easy to be used because assessment scenarios can be done through diagrams. Software verification was performed by comparing its result to SRS-19 and CROM software calculation results. Dose estimated by SRS-19 are higher compared to the result of developed software. However, these are still acceptable since dose estimation in SRS-19 is based on conservative approach. On the other hand, compared to CROM software, the same results for three scenarios and a non-significant difference of 2.25% in another scenario were obtained. These results indicate the correctness of our implementation and implies that the developed software is ready for use in real scenario. In the future, the addition of various features and development of new model need to be done to improve the capability of software that has been developed.